Recreational participation of children with Autism Spectrum Disorder (ASD) / Che Bon Ahmad and Nurul Raihana Ramzi - Ahmad, Che Bon; Ramzi, Nurul Raihana (UiTM Press, 2021)
Nature recreation is the recreation which require engagement with natural environment and settings. Previous research proven that recreation is important for people including the disabilities, towards achieving the quality of life. However, little is known about the development of recreation for People with Autism Spectrum Disorder (ASD. Thus, this research aimed to determine the effectiveness of nature recreation for children with ASD in a family with the objectives were to compare the changes in development of children with ASD in a family before and after participating in the nature recreation, and to identify the most preferable nature recreation activity for children with ASD in a family. A set of questionnaire surveys were distributed to a focus group called ‘Autism Malaysia’. This study showed, nature recreation can benefit children with ASD (aged from 0 to 12 years) and it is important for children development (social, intellectual, emotional and also physical). The children with ASD have positive changes in terms of communication and sociability components. However, for the physical behaviour, it showed the opposite findings; more risk and sign of ASD after participating in nature recreation. The result for each child may vary depending on the factors and nature recreation may not help to cure the ASD children completely. However, this study may help the family and caretaker of the children with ASD to use the nature recreation as the early intervention for their growth development. This research may help the planning development process in line with the Sustainable Development Goal which is social inclusion.